Ultrawideband electromagnetic metamaterial absorber utilizing coherent absorptions and surface plasmon polaritons based on double layer carbon metapatterns - Yongjune Kim (Nature Portfolio, 2021)
Abstract An ultrawideband electromagnetic metamaterial absorber is proposed that consists of double-layer metapatterns optimally designed by the genetic algorithm and printed using carbon paste. By setting the sheet resistance of the intermediate carbon metapattern to a half of that of the top one, it is possible to find an optimal intermediate metapattern that reflects and absorbs the EM wave simultaneously. By adding an absorption resonance via a constructive interference at the top metapattern induced by the reflection from the intermediate one, an ultrawideband absorption can be achieved without increasing the number of layers. Moreover, it is found that the metapatterns support the surface plasmon polaritons which can supply an additional absorption resonance as well as boost the absorption in a broad bandwidth. Based on the simulation, the $$90%$$ 90 % absorption bandwidth is confirmed from 6.3 to 30.1 GHz of which the fractional bandwidth is 130.77 $$%$$ % for the normal incidence. The accuracy is verified via measurements well matched with the simulations. The proposed metamaterial absorber could not only break though the conventional concept that the number of layers should be increased to extend the bandwidth but also provide a powerful solution to realize a low-profile, lightweight, and low cost electromagnetic absorber.